The impact of real economic activity on the effectiveness of monetary policy transmission: The case of Tunisia - Ons Mastour (Graduate Institute of International and Development Studies, 2020)
We study the relationship between the strength of the bank credit channel (BCC) of monetary policy transmission and real GDP growth in Tunisia using quarterly commercial bank-level data between 2008 and 2019. We find evidence of the existence of the bank credit channel in Tunisia in both its broad and strict senses. Classification of banks by total assets allows us to conclude that funding-constrained banks are very reactive to changes in the policy rate regardless of the economic cycle. However, identification of the strength of the BCC during different economic cycles is not possible in our case due to the lack of significance of the coefficients of interest. Furthermore, we find that the BCC operated exclusively through specific loan categories and banks during the sample period.
Keywords: E3; E5; G2; 330; Bank lending channel; monetary policy transmission; bank balance sheet channel; GDP growth